Neuroglial heterotopia of the middle ear: A case series and systematic literature review - Ahrendsen, Jared T (Surg Neurol Int, 2021)
BACKGROUND: The differential diagnosis for mass forming lesions of the middle ear is broad. While uncommon, neuroglial heterotopias can occur in the middle ear and can be a source of diagnostic confusion for clinician, radiologist, and pathologist alike. METHODS: We identified three cases of neuroglial heterotopia of the middle ear in our institutional archives from 2000 to 2020 and performed extensive histological and immunohistochemical characterization of the three lesions. We conducted a systematic literature review to identify 27 cases published in the English literature between the years 1980 and 2020. Only cases with histological verification of neuroglial heterotopia specifically involving the middle ear were included. We compiled the clinical, radiological, and histopathological findings for all 30 cases. RESULTS: Patients most frequently presented with chronic otitis media (40%), hearing loss (40%), or prior history of ear surgery or trauma (13%). The median age at surgery was 49 years with a male predominance (M:F 2:1); however, a bimodal age distribution was noted with an earlier onset (11 years or younger) in a subset of patients. Immunohistochemical characterization showed mature neuronal and reactive glial populations with low Ki67 proliferation index and chronic inflammatory infiltrates. There was no neuronal dysplasia or glial atypia, consistent with benign, nonneoplastic, mature glioneuronal tissue. CONCLUSION: Immunohistochemical characterization of these lesions and clinical follow-up confirms their benign natural history. Potential etiologies include developmental misplacement, trauma, and chronic inflammation/ reactive changes resulting in sequestered encephalocele.